A STUDY OF THE DETERMINANTS OF PERCEPTION ON THE GIRL CHILD IN ANDHRA, TELANGANA AND RAYALASEEMA REGIONS - BILQUIS; K.MAYURI (The Journal of Research ANGRAU, 2016)
The decline in child sex ratio (0-6 years) from 945 in 1991 to 927 in 2001 and further to 914 females per 1,000 males in 2011, the lowest since independence is cause for alarm, and serious policy re-think. This is despite legal provisions, incentive-based schemes, and media messages. This artificial alteration of our demographic landscape has implications for not only gender justice and equality but also social violence, human development and democracy. The present study (2013-14)focused on finding out the determinants of the perception on the girl child in the three regions of united Andhra Pradesh state. Sample consisted of 345men and women, 115 from each region were selected. The perception scores of the participants were related with the selected independent variables such as age, gender, education, social desirability, values and satisfaction with life using step down regression to find out the important determinants in each region. The findings revealed that number of years of education, social desirability and the values like self enhancement and conservation were found to be important determinants that influence the perception of the people on the girl child.